Update of the Translation of George Orwell’s Book “1984”. The Media Coverage - Yordanova, Vesela (Media and Language, 2025)
George Orwell’s novel “1984” has an established status as an emblem in the pantheon of literary anti-utopias. Modern readers can significantly associate the issues addressed in the book with current social phenomena. However, the project of adapting the translation of the novel to modern young readers is becoming a field of discussion. An emblematic example is the translation of Borislav Stefanov, published in 2021 as part of the “Project 48” campaign initiated by the online media “Az Cheta”. This paper includes a comparative analysis of part of the first chapter of the translations of Borislav Stefanov and Lydia Bozhilova (published in 1989) and presents the media coverage after the publication.